Sustainable Tourism Development Strategy Boonpring Andeman (SWOT and Business Model Canvas Approach) - Astriana, Yurika Brilyan; Wahjoedi, Wahjoedi; Soseco, Thomas (Program Pascasarjana Universitas Negeri Makassar, 2025)
Boonpring Andeman, located in Sanankerto Tourism Village, Malang Regency, holds significant potential as a sustainable tourism destination, featuring a bamboo forest, an arboretum with 115 bamboo species, and environmental education-based ecotourism. Despite receiving national and regional awards, the area still faces challenges related to accessibility, infrastructure, promotion, and community empowerment. This study aims to formulate sustainable tourism development strategies using a qualitative approach through SWOT analysis and the Business Model Canvas (BMC). Data were collected through interviews and observations, then analyzed descriptively. The findings indicate that development strategies focus on institutional strengthening, increasing community participation, and integrating conservation with educational values. The SWOT and BMC approaches successfully identified strategic priorities such as innovation in culturally-based tourism products, strengthening partnerships, and diversifying promotion to achieve a balance between economic, social, and ecological aspects.